Case in Kurdish dialects – south of Kurdistan - Ali Kamal Kareem, Diyar; Abdullah Abdul Hamee, Najat (Zanco Journal of Human Sciences, 2022)
Case in an original linguistic Case is an original linguistic phenomenon of many languages. It is a system whereby the form of word appearance or word order is changed in a sentence. Case exists in many languages, languages exhibit different types of cases. Case, in traditional grammar, has been used with the intent to define nouns. The significance of case lies in morphological markers. This phenomenon, case, is reflected in some Kurdish dialects. The current study is entitled “Case in Kurdish Dialects, Southern Kurdistan as an example”. The aim of the study is to present gender and grammatical cases in the geographical division of Kurdish dialects in order to draw the map of Kurdish dialects’ cases. The importance of the study is that it highlights the types of cases in Kurdish dialects. Reference: یەکەم- نامەى ئەکادیمییەکان - ئیبراهیم,شیلان رەحیم(2004),شێوازى قسەکردنى ژن لەزمانى کوردیدا,نامەى ماستەر,کۆلێژى زمان, زانکۆى سلێمانى. - ئەحمەد,مزگین عبدالرحمان(2006),دۆخى ئێرگەتیڤى لەزمانى کوردیدا(کرمانجى سەرو),نامەى ماستەر,کۆلێژى پەروەردە بۆزانستە مرۆڤایەتییەکان,هەولێر:زانکۆى سەلاحەدین. - ئەحمەد,غازى فیصل(2015),دۆخى ڕێزمانى لەزمانى کوردیدا,نامەى ماستەر,کۆلێژى پەروەردە بۆ زانستە مرۆڤایەتییەکان,هەولێر:زانکۆى سەلاحەدین. - حاجى,ڤیان سلێمان(2009),کەرەسە بەتاڵەکان لەڕوانگى تیۆرى دەستەڵاات و بەستنەوە(شێوازى کرمانجى سەرو),هەولێر:بڵاوکراوەى ئەکادیمیاى کوردى. - خدر,حەیدەر حاجى(2010),تایبەتمەندییە مۆرفۆلۆژییەکانى زمانى کوردى لەڕوانگەى پۆلینى مۆرفۆلۆژیانەى زمانەکەوە,نامەى ماستەر,کۆلێژى زمان,زانکۆى سەلاحەدین. - سەعید,یوسف شەریف(1990),دۆخەکانى ژێرەوە لاى فیلمۆر و هەندێ لایەنى ڕستەسازى کوردى,نامەى ماستەر,کۆلێژى ئاداب,زانکۆى سەلاحەدین. - مەعروف,عبدالجبار مستەفا(2009),دروستەى ڕستەى ئاڵۆز لەزمانى کوردیدا,نامەى دکتۆرا,کۆلیژى زمان,زانکۆى سلێمانى. دووەم: کتێب 1- بەزمانى کوردى - ئەمین,وریا عومەر(2004),چەندئاسۆیەکى ترى زمانەوانى,بەرگى یەکەم,هەولێر:دەزگاى ئاراس. - تۆفیق,قەیس کاکل(2020),زمان و ئاین,بەشى یەکەم,دهۆک :چاپخانەى ماد. - خۆشناو,نەریمان عبدالله(2014 ),دیالێکت و زمان ,چاپى دووەم, زیادکراو و پوختکراو,هەولێر:چاپخانەى هێڤى. - عەلى,طالب حسین(2014),زانستى زمان و زمانى کوردى,چاپى یەکەم,هەولێر:چاپخانەى ڕۆژهەڵات. - عوسمان , مەزن( ),هەندێ بەراورد و سەرنجى زمانەوانى, - قادر,صباح رشید(2009),هەندێ لایەنى ڕێزمانى دەستەڵات و بەستنەوە لەزمانى کوردیدا,هەولێر:چاپخانەى حاجى هاشم. - کۆڕى زانیارى, (1976), رێزمانى ئاخاوتنى کوردى, بەغدا:چاپخانەى کۆڕى زانیارى کورد. - مارف,ئاورەحمان حاجى(1979),مۆرفۆلۆژى ناو,بەشى یەکەم, بەغدا: کۆڕى زانیارى عێراق دەستەى کورد. - مەحوى,موحەمەد(2001),ڕستەسازى کوردى,چاپخانەى زانکۆى سلێمانى. - موحەمەد,حاتم ولیا(2009),پەیوەندییە ڕۆنانییەکانى نواندنە سینتاکسییەکان,چاپى یەکەم,دهۆک:چاپخانەى خانى. - مەحوى,موحەمەد(2011),بنەماکانى سینتاکسیی کوردى,بەرگى یەکەم,سلێمانى:چاپخانەى پەیوەند. - ناوخۆش,سەلام(2018),لەبارەى مۆرفۆلۆژى و سینتاکس و مۆرفۆسینتاکس,لێکۆڵینەوەیەکى شیکارییە بەکەرەسەى کوردى, هەولێر:چاپخانەى شەهاب - هەورامى,موحەمەد ئەمین(1981),دیالێکتى زمانى کوردى لەتەرازوى بەراوردا,بەغدا:دەزگاى ڕۆشنبیرى و بڵاوکردنەوەى کورد. 2- بەزمانى عەرەبى - زکریا,میشال(1983),علم اللغة التحدیث ,المبادىء والأعلام,المؤسسة الجامعیە للدراسات والنشر والتوزیع,بیروت:لبنان. 3- بەزمانى ئینگلیزى - Anderson, J .M (1987).Case Grammar and the Local List Hypothesis, Concepts of Case, Tubingen. - Blake, Barry (1994).Case Cambridge, University Press. - Chomsky, Noam (1981).Lecture On Government and Binding, The Pisa Mouton Degrayter, New York. - Chomsky, Noam (1986). Knowledge of Language . Its Nature, Origin Use Pager, New York. - Crystal, David (1991). A Dictionary of Linguistics and Phonetics 3rd edition , Black Well Publisher, Ltd.Uk. - Culicover, Peter (1997).Principles And Parameters: An Introduction to Syntactic Theory, Oxford University. New York. - Crystal, David (1991). A Dictionary of Linguistics and Phonetics 6rd Edition, Black Well - Fillmore, Charles (1965). Indirect Object Constructions In English And The Ordering Transform Motions, Mouton. - Farokhpy (1998).Government And Biding Chomsky Language Theory, Tehran: Somkhan. - Grime, Scott (2005). The Lattice Of Case And Agentivity, MSc In Logic, University It Van Amsterdam. - O, Grady , William (2005). Archibald, Aronoff, Mand and Miller, Contemporary Linguistics 5th Edition .Usa: Bedford. - Trask , L (1993). A Dictionary of Grammatical Terms In Linguistics, Rout ledge, London And New York. 3- گۆڤار - ئەمین,وریا عومەر(2015),دۆخ و ئەرکى بەشەکانى ڕستە,گۆڤارى ئەکادیمى ,ژمارە 34,هەولێر. - تۆفیق,قەیس کاکل(2014),سێکسیزم لەزمانى کوردیدا,گۆڤارى توێژەر ژمارە(؟),زانکۆى سۆران.